Does leisure‐time physical activity attenuate or eliminate the positive association between obesity and high blood pressure?. Issue 5 (25th April 2018) - Werneck, André O; Oyeyemi, Adewale L; Gerage, Aline M; Cyrino, Edilson S; Szwarcwald, Célia L; Sardinha, Luís B; Silva, Danilo R
Abstract : We examine the joint association of weight status and leisure‐time physical activity on high blood pressure in a nationally representative sample of adults and older adults in Brazil. This was a national cross‐sectional survey conducted in Brazil in 2013 (Brazilian Health Survey). The sample consisted of 59 402 participants (56% women, aged 18 to 100 years). Outcome was objectively assessed blood pressure. Body mass index (BMI) was objectively measured, while self‐reported information on leisure‐time physical activity, TV viewing, chronological age, race, educational status, tobacco smoking, sodium consumption, and hypertension medication was obtained using questionnaires. Logistic regression analysis with adjusted odds ratio was conducted to test the joint association of BMI and leisure‐time physical activity categories on high blood pressure. Overall, compared to normal weight (NW) and physically active group, the NW/inactive (OR = 1.28; 1.04 to 1.58), overweight/active (OR = 1.38; 1.08 to 1.78), overweight/inactive (OR = 1.89; 1.53 to 2.33), obese/active (OR = 2.19; 1.59 to 3.01) and obese/inactive (OR = 2.54; 2.05 to 3.15) groups were 28% to 254% more likely to have high blood pressure. The attenuation and high blood pressure was greater for women and adults than for men and older adults. Thus, leisure‐time physical inactivity and being overweight and obesity were associated with high blood pressure in Brazilian population. Engaging in sufficient level of physical activity during leisure could attenuate, but not eliminate, the negative influence of obesity on high blood pressure in Brazilian adults and older adults.